Educação infantil de dekasseguis: análise intercultural de um estudo de caso - Nomiso, Cecília Massako [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Since the beginning of the century XX, dekassegui's reverse migration movement incresed the number of Japanese Brazilians in Japan, and consequently, the number of school-age children. The need for providing similar education, avoiding traumatic experiences or early school leaving, led the installation of Brazilian schools in Japan, benefiting only a part of this population. Due to this context, this research decided to analysis how childhood education is held for the Japanese Brazilian children, nationally and internationally. The field research was made in two Brazilian schools in Japan and also a municipal school in Bauru city in Brazil, aimed to know specific details, limitations and the educational quality level provided in these institutions - by looking at the whole procedure of how to access, be admitted and become a permanent at the institute. The data collected was based on the national quality in kindergarten indicators and demonstrated some difficult situations faced by dekassegui population. These situations were generated by a lack of resources: material, financial and qualified educators involved in this task due to the wide culture diversity. The study case describes a real experience of a Brazilian child born in Japan who transits between the two countries with different cultures

Desde o início do século XXI, o movimento dekassegui inverso, elevou o número de nikkeis brasileiros no Japão e, consequentemente, o número de crianças na idade escolar. A necessidade de se proporcionar educação, de acordo com o sistema brasileiro a essas crianças, para se evitar experiências traumáticas ou abandono escolar, levou a instalação de escolas brasileiras em solo japonês, atendendo parcialmente essa população. Neste contexto, esta pesquisa teve como questão norteadora, analisar como é realizada a Educação Infantil para os filhos de dekasseguis, no âmbito nacional e internacional. A observação em campo, em duas escolas brasileiras no Japão, e em uma escola municipal de Bauru, no Brasil, teve como objetivo geral conhecer as especificidades, limitações e o nível de qualidade educacional proporcionado nestas instituições, desde o acesso, acolhimento e permanência. Por meio de coleta de dados, fundamentada no documento nacional Indicadores de Qualidade na Educação Infantil, foram observados e revelados, situações e dificuldades enfrentadas pela população dekassegui, geradas pela falta de recursos materiais, financeiros e de formação para os educadores envolvidos nesta tarefa de educar em meio à diversidade cultural. A realidade vivenciada, no estudo de caso, por uma criança brasileira nascida no Japão, proporcionou o conhecimento de situações comuns para essas crianças, que transitam entre os dois países e suas interculturalidades
Keywords: Educação de crianças; Dekasseguis; Multiculturalismo; Education